2002
DOI: 10.2165/00003495-200262080-00002
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cutaneous Erythrasma

Abstract: Corynebacterium minutissimum is the bacteria that leads to cutaneous eruptions of erythrasma and is the most common cause of interdigital foot infections. It is found mostly in occluded intertriginous areas such as the axillae, inframammary areas, interspaces of the toes, intergluteal and crural folds, and is more common in individuals with diabetes mellitus than other clinical patients. This organism can be isolated from a cutaneous site along with a concurrent dermatophyte or Candida albicans infection. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 39 publications
1
57
0
1
Order By: Relevance
“…Topical antibiotics such as fusidic acid or clindamycin suffi ce in limited lesions. More extensive involvement responds rapidly to oral erythromycin [ 81 ].…”
Section: Erythrasmamentioning
confidence: 99%
“…Topical antibiotics such as fusidic acid or clindamycin suffi ce in limited lesions. More extensive involvement responds rapidly to oral erythromycin [ 81 ].…”
Section: Erythrasmamentioning
confidence: 99%
“…Candidiasis can be differentiated from tinea cruris by its irregular border with satellite lesions and scrotal involvement (which often appears bright red and shiny). Cutaneous erythrasma, a cutaneous bacterial infection caused by Corynebacterium minutissimum, can easily mimic tinea cruris as 30% of patients with interdigital erythrasma have been found to have a coexisting dermatophyte or C. albicans infection, usually noted in the third and fourth interspaces [55].…”
Section: Tinea Corporis and Tinea Crurismentioning
confidence: 99%
“…The latter are used solely for symptomatic care. Tinea corporis and tinea cruris can be effectively treated systemically by fluconazole 50-100 mg/day or 150 mg once weekly for 2-3 weeks, by itraconazole 100 mg/day for 2 weeks or 200 mg/day for 7 days and by terbinafine 250 mg/day for 1-2 weeks [55][56][57]. In one smaller study that examined fluconazole at a dose of 150 mg once-weekly for tinea corporis or tinea cruris, the authors found an overall cure rate of 95% and noted that 70% of patients required two doses for cure, 20% of patients required three doses for cure and 10% required four doses [56].…”
Section: Tinea Corporis and Tinea Crurismentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by erythematous, brown, scaly patches and maceration, and exhibits coral-red fluorescence under Wood's light (5)(6)(7)(8). There is no standard method of treatment for erythrasma, and a variety of oral, topical and adjunctive therapy models are used (9). In this study, our aim was to compare the effectiveness of the treatments with erythromycin, single-dose clarithromycin and topical fusidic acid with the double-blind, randomized, placebo-controlled method in patients with erythrasma.…”
Section: Introductionmentioning
confidence: 99%